2019
DOI: 10.1042/bsr20181730
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid improves parthenogenetic embryo development through TET proteins in mice

Abstract: The TET (Ten-Eleven Translocation) proteins catalyze the oxidation of 5mC (5-methylcytosine) to 5hmC (5-hydroxymethylcytosine) and play crucial roles in embryonic development. Ascorbic acid (Vc, Vitamin C) stimulates the expression of TET proteins, whereas DMOG (dimethyloxallyl glycine) inhibits TET expression. To investigate the role of TET1, TET2, and TET3 in PA (parthenogenetic) embryonic development, Vc and DMOG treatments were administered during early embryonic development. The results showed that Vc tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Immunofluorescence (IF) staining is an important method for measuring protein expression in embryos, and has been used in our previous studies (Gao et al, 2019; Hao et al, 2019; Liang et al, 2017; Yuan et al, 2017) and other related studies (Amouroux et al, 2016; Inoue & Zhang, 2011; Sakashita et al, 2014). To detect expression of apoptotic proteins in MII oocytes by IF staining in this study, we analyzed the P53 level of 21 MII oocytes of 100 μM PB1 group and 21 MII oocytes of control group, the caspase‐3 level of 24 MII oocytes of 100 μM PB1 group and 23 MII oocytes of control group.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence (IF) staining is an important method for measuring protein expression in embryos, and has been used in our previous studies (Gao et al, 2019; Hao et al, 2019; Liang et al, 2017; Yuan et al, 2017) and other related studies (Amouroux et al, 2016; Inoue & Zhang, 2011; Sakashita et al, 2014). To detect expression of apoptotic proteins in MII oocytes by IF staining in this study, we analyzed the P53 level of 21 MII oocytes of 100 μM PB1 group and 21 MII oocytes of control group, the caspase‐3 level of 24 MII oocytes of 100 μM PB1 group and 23 MII oocytes of control group.…”
Section: Methodsmentioning
confidence: 99%
“…Several epigenetic modifications, such as DNA methylation and histone modification, have been observed to be lacked during the development of parthenogenetic embryos because of the deficiency of HDAC1 and DNMT1 expression [48]. In addition, downregulated expression of TET1, TET2, and TET3 has been confirmed in parthenogenetic embryos [49]. To detect CENPF function in both IVF and parthenogenetic embryos, MII oocytes and zygotes were used for CENPF knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…AA, as an irreplaceable cofactor, can effectively enhance the activity of the TET3 enzyme and promote the demethylation of active DNA (Gao et al, ). A previous study showed that in sheep IVF preimplantation embryos, the transcriptional level of TET3 was highest in the 2‐cell stage and gradually decreased in the 4‐cell, 8‐cell, and morula stages until the blastocyst stage, where it was the lowest.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, TET3 fluorescence intensity analysis showed that TET3 gradually increased from the 2cell to the morula stage and was weakly present in the blastocyst stage, unlike the results of the study in cattle, TET3 is expressed in the cytoplasm at all stages of IVF preimplantation embryo development in the yak. Perhaps the previous results can explain this(Yuko et al, 2012), first, there is a highly expressed activation-induced cytidine deaminase (Aid) in the development of yak embryos, and coexpression pattern with TET, secondly, the shuttle function of Aid transfers nuclear TET3 protein to the cytoplasm, and in this study the gene expression trend of TET3 was consistent with the fluorescence intensity analysis results, which indicates that the TET3 protein regulates the mechanism of active DNA demethylation by subcellular localization.AA, as an irreplaceable cofactor, can effectively enhance the activity of the TET3 enzyme and promote the demethylation of active DNA(Gao et al, 2019). A previous study showed that in sheep IVF preimplantation embryos, the transcriptional level of TET3 was highest in the 2-cell stage and gradually decreased in the 4-cell, 8-cell, and morula stages until the blastocyst stage, where it was the lowest.…”
mentioning
confidence: 99%